Is cerebral small vessel disease a central nervous system interstitial fluidopathy? - Abdul Hamid, Hafizah; Hambali, Aqilah; Okon, Udemeobong; Che Mohd Nassir, Che Mohd Nasril; Mehat, Muhammad Zulfadli; Norazit, Anwar; Mustapha, Muzaimi (Elsevier B.V., 2024)
A typical anatomical congregate and functionally distinct multicellular cerebrovascular dynamic confer diverse blood-brain barrier (BBB) and microstructural permeabilities to conserve the health of brain parenchymal and its microenvironment. This equanimity presupposes the glymphatic system that governs the flow and clearance of metabolic waste and interstitial fluids (ISF) through venous circulation. Following the introduction of glymphatic system concept, various studies have been carried out on cerebrospinal fluid (CSF) and ISF dynamics. These studies reported that the onset of multiple diseases can be attributed to impairment in the glymphatic system, which is newly referred as central nervous system (CNS) interstitial fluidopathy. One such condition includes cerebral small vessel disease (CSVD) with poorly understood pathomechanisms. CSVD is an umbrella term to describe a chronic progressive disorder affecting the brain microvasculature (or microcirculation) involving small penetrating vessels that supply cerebral white and deep gray matter. This review article proposes CSVD as a form of “CNS interstitial fluidopathy”. Linking CNS interstitial fluidopathy with CSVD will open a better insight pertaining to the perivascular space fluid dynamics in CSVD pathophysiology. This may lead to the development of treatment and therapeutic strategies to ameliorate the pathology and adverse effect of CSVD.